mathdad
Full Member
- Joined
- Apr 24, 2015
- Messages
- 925
Solve the inequality.
x^2 - x - 6 < 0
Here I go.
Replace < with the = sign, set to 0 and factor.
(x - 3)(x + 2) = 0
x = 3 and x = - 2
Between -2 and 3, the function will always be greater than 0 or always less than 0.
I will pick a number between
-2 & 3. How about 0? I love using 0 as a substitute value.
Let x = 0
x^2 - x - 6 < 0
(0)^2 - 0 - 6 < 0
- 6 < 0
I understand this to mean that the given function is less than 0 between -2 and 3.
I conclude from this finding that x^2 - x - 6 is less than 0 in the interval (-2, 3).
So, how did I do?
x^2 - x - 6 < 0
Here I go.
Replace < with the = sign, set to 0 and factor.
(x - 3)(x + 2) = 0
x = 3 and x = - 2
Between -2 and 3, the function will always be greater than 0 or always less than 0.
I will pick a number between
-2 & 3. How about 0? I love using 0 as a substitute value.
Let x = 0
x^2 - x - 6 < 0
(0)^2 - 0 - 6 < 0
- 6 < 0
I understand this to mean that the given function is less than 0 between -2 and 3.
I conclude from this finding that x^2 - x - 6 is less than 0 in the interval (-2, 3).
So, how did I do?